Aggregation of polyQ-extended proteins is promoted by interaction with their natural coiled-coil partners - Petrakis, Spyros (Blackwell Publishing Ltd, 2013)
Polyglutamine (polyQ) diseases are genetically inherited neurodegenerative disorders. They are caused by mutations that result in polyQ expansions of particular proteins. Mutant proteins form intranuclear aggregates, induce cytotoxicity and cause neuronal cell death. Protein interaction data suggest that polyQ regions modulate interactions between coiled-coil (CC) domains. In the case of the polyQ disease spinocerebellar ataxia type-1 (SCA1), interacting proteins with CC domains further enhance aggregation and toxicity of mutant ataxin-1 (ATXN1). Here, we suggest that CC partners interacting with the polyQ region of a mutant protein, increase its aggregation while partners that interact with a different region reduce the formation of aggregates. Computational analysis of genetic screens revealed that CC-rich proteins are highly enriched among genes that enhance pathogenicity of polyQ proteins, supporting our hypothesis. We therefore suggest that blocking interactions between mutant polyQ proteins and their CC partners might constitute a promising preventive strategy against neurodegeneration.